THE SOCIAL CONSTRUCTION PATTERN OF RELIGIOUS MODERATION IN AN INCLUSIVE SOCIETY (A CASE STUDY OF PUNTUKDORO VILLAGE, MAGETAN) - Muslim, Abu; Faristiana, Andhita Risko; Arafah, Ulfa Binti (IAIN PONOROGO, 2024)
This research aims to analyze the factors contributing to the creation of religious harmony among different faith communities in Moderation Village, Puntukdoro Village, Magetan, East Java. The study is grounded in Berger and Luckman's social construction theory, which posits that social reality is shaped through social interactions and the collective construction of individuals and communities. The philosophy of